Measures of stimulant medications: A population-based study in Alberta, Canada - Cerina Dubois; Ming Ye; Olivia Weaver; Salim Samanani; Ed Jess; Fizza Gilani; Dean T. Eurich (Emerging Trends in Drugs, Addictions, and Health)
Objectives: Stimulants are a class of drugs approved for the treatment of attention-deficit hyperactivity disorder (ADHD) and narcolepsy. However, they are also often used “off-label” as adjunct therapies for the treatment of obesity and depression. The objective of this study is to summarize how stimulant use is globally measured in the literature and to explore rates of stimulant use in Alberta, Canada. Methods: A traditional narrative literature review was conducted to summarize global methods of stimulant assessment. Then using definitions guided by the literature and current regulatory bodies in Alberta, we conducted a series of descriptive analyses to assess how frequent stimulant use was in Alberta patients from 2019 to 2021: 1) number of dispenses by year; 2) average days of drug supply; 3) proportion of days covered (PDC); and 4) defined daily dose (DDDs). Results: In the literature review, the most frequently used measures of stimulant drug use were trends over time (prevalence), types of drug use, and dispensations of prescriptions. In all, there is a global trend of increased use of stimulants among both adults and children. In Alberta, 173,789 patients were prescribed stimulant medication in 2019–2021, representing approximately 4 % of the entire Alberta population. Overall, 61.1 % were between the ages of 10–34 and 46.8 % were female. The number of dispensations rose from 713,896 in 2019 to 973,930 in 2021 – with up to 43 % being lisdexamfetamine stimulant dispenses. Conclusions: Although stimulant use in AB was measured using similar trend estimates as the literature, there is a lack of research to support whether these measures are accurate and effective at the population-level. Future steps to standardize both medical and nonmedical use of prescription stimulants are warranted in efforts to fully quantify both benefits and risks associated with stimulant use.